Language Variations On Signboards in the Berastagi Tourism Area - Emeninta Prihartini Sitepu; Mulyadi; Mhd Pujiono; Dardanila (proceedings.icesy, 2026)
This study aims to describe the use of language variations on signage in the Berastagi tourism area. This research method uses descriptive qualitative data collection techniques, using observation and photography. The data in this study are the texts appearing on signage in the Berastagi tourism area. The analysis of 32 data points revealed variations in monolingual language (Indonesian and English), bilingual (Indonesian–English and Indonesian–Karo), and multilingual (Indonesian–English–Karo). Indonesian dominates the language use on signage, demonstrating its status as the primary language and primary means of communication for visitors. English represents a global orientation, and Karo reflects local identity and culture.